Pelatihan Preposisi Tempat Bahasa Inggris In, On, dan At Untuk Siswa Lembaga Pendidikan Pramugari Total Source Development Yogyakarta - Wijayanti, Anita; Jaya, I Made Laut Mertha; Pujianto, Defi (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2025)
Prepositions are a topic in English that is considered difficult to master. Linguistic differences between Indonesian and English are considered one of the reasons why Indonesian English speakers find it difficult to use the correct English prepositions. Confusions often arise when Indonesian learn the prepositions of place in, on, and at, because in Indonesian, all three are translated as the preposition